NanoTag Nanobody Tools for Drosophila In Vitro and In Vivo Studies. Issue 12 (26th December 2022) - Kim, Ah‐Ram; Xu, Jun; Cheloha, Ross; Mohr, Stephanie E.; Zirin, Jonathan; Ploegh, Hidde L.; Perrimon, Norbert
Abstract: Nanobodies have emerged as powerful protein‐binding tools to uncover protein functions. Using functionalized protein binders, proteins of interest can be visualized, degraded, delocalized, or post‐translationally modified in vivo . We recently reported the use of two short peptide tags, 10‐aa 127D01 and 14‐aa VHH05, and their corresponding nanobodies, Nb127D01 and NbVHH05, for both in vitro and in vivo studies in Drosophila . Here, we provide detailed protocols for nanobody production and for visualization of proteins of interest in either fixed or live samples. In addition, we include protocols for endogenous protein tagging using CRISPR‐mediated genome engineering. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Nanobody production in S2 cells Basic Protocol 2 : Nanobody expression and purification in bacterial cells Basic Protocol 3 : Immunostaining with nanobodies Basic Protocol 4 : Immunoblotting with nanobodies Basic Protocol 5 : Immunoprecipitation with nanobodies prepared from S2 cells Basic Protocol 6 : Immunoprecipitation with nanobodies prepared from bacteria Basic Protocol 7 : NbVHH05 and Nb127D01 used as chromobodies Basic Protocol 8 : NanoTag trap as a method to alter protein localization Support Protocol : CRISPR‐mediated tagging of endogenous genes with NanoTags